Graduate Students’ Perceived Supervisor Support and Innovative Behavior in Research: The Mediation Effect of Creative Self-Efficacy - Han, Jiying; Liu, Nannan; Wang, Feifei (Frontiers in Psychology, 2022)
With increased global competition and the advent of the knowledge economy, developing graduate students’ ability to innovate in their research has become a core focus of graduate education. Graduate students’ perceived help and assistance from supervisors is one of the key resources for research innovation. This study explored the relationships between graduate students’ perceived supervisor support and their innovative behavior in research, and examined the mediation effect of creative self-efficacy, their confidence in abilities to generate creative ideas or produce creative outcomes. Survey data were collected from a sample of 996 Chinese graduate students. The results revealed that academic support was negatively related to idea generation and idea search; personal support was positively related to overcoming obstacles; autonomy support was positively related to all factors of innovative behavior except overcoming obstacles and innovation outputs. The mediation analysis suggested that creative self-efficacy significantly mediated the relationship between academic support and graduate students’ innovative behavior in research. The results of this study highlight the significance of both supervisor support and creative self-efficacy in developing graduate students’ research innovation. The findings have significant implications for stimulating students’ research innovation and for improving the quality of graduate education.